2021
DOI: 10.3389/fimmu.2021.690623
|View full text |Cite
|
Sign up to set email alerts
|

From Mesenchymal Stromal/Stem Cells to Insulin-Producing Cells: Immunological Considerations

Abstract: Mesenchymal stem cell (MSC)-based therapy for type 1 diabetes mellitus (T1DM) has been the subject matter of many studies over the past few decades. The wide availability, negligible teratogenic risks and differentiation potential of MSCs promise a therapeutic alternative to traditional exogenous insulin injections or pancreatic transplantation. However, conflicting arguments have been reported regarding the immunological profile of MSCs. While some studies support their immune-privileged, immunomodulatory sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 168 publications
(185 reference statements)
0
8
0
Order By: Relevance
“…Recent studies in laboratory and animal models have shown that mesenchymal stem cells play an effective role in regulating immunity in autoimmune diseases such as rheumatoid arthritis, systemic lupus erythematosus, and encephalitis [17,18]. Recently, many researchers have become interested in adult stem cells because they can transform into many tissues and there is no moral concern about using them [19,20].…”
Section: Research Articlementioning
confidence: 99%
“…Recent studies in laboratory and animal models have shown that mesenchymal stem cells play an effective role in regulating immunity in autoimmune diseases such as rheumatoid arthritis, systemic lupus erythematosus, and encephalitis [17,18]. Recently, many researchers have become interested in adult stem cells because they can transform into many tissues and there is no moral concern about using them [19,20].…”
Section: Research Articlementioning
confidence: 99%
“…The underlying mechanism is mainly associated with modulating autoimmune responses against islets. In addition to suppressing pathogenic CD8 + T cells, T helper 1 (Th1) cells and T helper 17 (Th17) cells [ 9 , 10 ], MSCs can also promote regulatory T cells (Tregs) through paracrine effects, direct cell receptor interactions or mitochondrial transfer [ 11 , 12 ]. Because islets are highly vascularized mini-organs, the promotion of angiogenesis by MSCs in islets is another potential mechanism in T1D [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…MSCs can also be induced to differentiate into insulin‐secreting cells and adjust the state of the body's immune system, which is expected to have potential in the treatment of endocrine diseases such as diabetes. [ 26 ] MSCs have the ability to differentiate into osteoblasts, adipocytes, and chondrocytes, and have strong effects on the repair and regeneration of cartilage and bone defects [ 27 ] ( Figure ).…”
Section: Marketization Of Msc‐based Therapeutic Productsmentioning
confidence: 99%